P‐51: A Compact a‐IGZO TFT‐Based Digital‐to‐Analog Converter for Flexible Displays. Issue 1 (June 2015) - Li, Xiuling; Geng, Di; Mativenga, Mallory; Jang, Jin
Abstract : We report the design and fabrication of an amorphous‐indiumgallium‐zinc‐oxide (a‐IGZO) thin‐film transistor (TFT)‐based 4‐bit digital‐to‐analog converter (DAC) for flexible displays. The DAC consisting 2 capacitors and 10 TFTs is 130 µm in width, compact enough to be fitted in one column of data drivers. The DAC shows good linearity under mechanical bending radius of 2 mm, making it applicable to flexible active‐matrix displays.